Prevalensi Kesulitan Belajar Peserta Didik di Madrasah Aliyah Negeri I Bandar Lampung - Defriyanto, Defriyanto; Dermawan, Oki (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2018)
To improve the learning achievement of students in school, it is necessary to provide assistance that can overcome them in the learning process. But it is not easy. It is better to help learners in overcoming learning difficulties, the number of occurrences of participants who have learned difficulties. Measuring the prevalence of learning difficulties in madrasas is necessary, as this will be related to the diagnosis of learning difficulties and what programs are appropriate to learners. By knowing the prevalence of learning difficulties learners in madrasah, it will help teachers in providing appropriate assistance to these learners. Madrasah Aliyah Negeri I Bandar Lampung is a madrasah Aliyah which has a lot of students. Based on the results of interviews with teachers counseling and guidance in the madrasah there are numbers of students whose learning achievement are low and have difficulty learning (Interview with Miss Dina Kurniasih). The formulation of this research problem: How to profile students's learning difficulties in MAN I Bandar Lampung? and How much is the prevalence of learning difficulties in MAN I Bandar Lampung? Based on the results of data analysis, this study can be concluded that the prevalence of learning difficulties in Madrasah Aliyah Negeri I Bandar Lampung is 26, 2%. The prevalence of learning difficulties is more prevalent in Gentelmant students than in female students. While the residence of students and departments does not determine the prevalence of learning difficulties. It may be said that place of residence and departement of students do not show differences in the prevalence of learning difficulties experienced of the students